Политический вербатим в современной русской драматургии - Kurant, Elena (Studia Rossica Posnaniensia, 2023)
The aim of this paper it to discuss the techniques employed in modern political Russian verbatim drama, as well as in their performances. Modern verbatim drama seeks to stay relevant and up-to-date by referring to taboos, radical social controversies, and political incidents. So, it becomes an important event of not only cultural but also social life, and it exerts a strong impact on modern Russian society. The aesthetics of the modern verbatim drama is aimed at representing the reality which is absent from official discourse. Such texts as One hour eighteen minutes by Elena Gremina, Three quarters of sadness (Bolotnaya square case) by Polina Borodina, The last party by Anna Dobrovolskaya, and New Antigone by Elena Kostyuchenko openly explore the issues which do not function as part of the public discourse. Thus, they capture the traumatic experiences in order to overcome traumas. These texts take the traumatic events of current political and public life out of the marginal area, and they acquire the status of social statements which give hope for political and social changes, and give rise to unofficial discourse allowing the readers as well as the viewers to define their own opinion related to the traumatizing events.